Technology Adoption with Exit in Imperfectly Informed Equity Markets - Tinn, Katrin (American Economic Review, 2010)
This paper focuses on the importance of equity markets in facilitating the exit of entrepreneurs investing in technology. Entrepreneurs' willingness to invest and aggregate output is affected in two opposite ways. First, uncertainty about equity price or lack of market liquidity discourages technology adoption. This can explain slow technology adoption and limited participation by venture capitalists in underdeveloped equity markets. Second, fast adoption is a positive signal to imperfectly informed equity market participants. This provides a rational explanation for overpricing technology stocks and overinvestment in developed markets. Fast adoption is most probable at an intermediate quality of information. (JEL D82, E23, G12, G31, G32, O33)